2018
DOI: 10.4314/jmbs.v6i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Profiling urinary tract infections bacteria among elderly population in a Nigerian Teaching Hospital

Abstract: There have been conflicting reports about prevalence of Urinary Tract Infections (UTIs) causing bacteria in elderly in recent times. This study aims to evaluate the prevalence and resistance pattern of UTIs causing bacteria in elderly Nigerian patients. A prospective cross-sectional study was carried out among elderly patients attending the general and medical outpatients’ clinics of Olabisi Onabanjo University Teaching Hospital, Sagamu, Nigeria. Patients aged 60 years and above with at least two signs of UTIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The variations in the structure and microbiota between male and female genitourinary systems may play a role in the preponderance of positive culture among females [22,23]. However, in another study done in other part of Nigeria, majority of the study participants were males [10]. In addition, it was discovered in this study that elderly people between the ages of 60 and 70 had higher rates of UTI, which supports the findings of another study in Southern Nigeria [11].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The variations in the structure and microbiota between male and female genitourinary systems may play a role in the preponderance of positive culture among females [22,23]. However, in another study done in other part of Nigeria, majority of the study participants were males [10]. In addition, it was discovered in this study that elderly people between the ages of 60 and 70 had higher rates of UTI, which supports the findings of another study in Southern Nigeria [11].…”
Section: Discussionsupporting
confidence: 84%
“…Among the uropathogens analyzed from the retrospective study, Staphylococcus aureus was the most common microorganism isolated from the urine culture of the elderly. This finding was not in keeping with finding from other studies were E. coli and Klebsiella species were attributed as the most common organism causing UTI among the elderly [10,11,18,22,24]. However, other studies done found Staphylococcus aureus to be majorly responsible for the UTI [15][16][17].…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations